Pengaruh Total Aktiva, Jumlah Sekuritas, Perputaran Portofolio, Laba/Rugi Operasi Dan Opini Akuntan Terhadap Audit Delay Pada Produk Reksa Dana Di Indonesia - Joicenda Nahumury (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstrackThis study empirically examined the effect of several company & audit characteristics on audit report lag or audit delay. Determinants of audit delay in mutual funds were chosen as an object of investigation. The purpose of this study to reveal that those variables have significant effect on audit delay simultaneously or partially. Samples are selected by purposive sampling method. The results of multiple linear regressions show that all of the explanatory variables influences audit delay simultaneously. The rest of variables do not appear to have any bearing on mutual fund audit delay. This Result is suggested for auditor to perform the audit more efficient and effective to get audit report timely, for BAPEPAM-LK as regulator to review again the deadline of audited financial statements delivery of mutual funds, for the future researcher to be reference in developing investigation.